Bad faith: the psychological life of a satanist who committed murder - Du Toit, Jacobus Petrus (Rhodes University, Faculty of Humanities, Department of Psychology, 2002)
Traditional methods of psychological and forensic research fail to adequately provide an account of the psychological meaning that perpetrators of crime derive when appropriating their actions to Satanic involvement. In February 2001, a young man appeared in a South African High Court and testified that he had committed murder as a result of his involvement in Satanism. The aim of this study is to gain a phenomenological understanding of how this man appropriates the act of murder to involvement in Satanism. A review of literature elucidates Satanism as a context for meaning, provide a framework for defining murder as a criminal act, and situate this study in the broader field of phenomenological-existential, psychological research. An emergent design case-study approach was applied to data gathered from a single subject, by means of a three-interview series. An empirical phenomenological methodology was used during the interpretive phase to arrive at both a descriptive account of the subject's phenomenological experience and how the eidetic structure of the experience of Satanism as a context tor meaning emerged. A discussion of the subject's appropriation of murder with Satanism illustrates how the subject imposed a dichotomy of good and bad on his life-world in an attempt to derive meaning from his experience of inadequacy. Involvement with Satanism is meaningful, in that it affords its followers an increased sense of power, a safe environment to explore individuality, shared responsibility associated with exercising free choice, social situatedness and an affirmation of being through an increased awareness of finitude. The research subject experienced committing murder as an act of loyalty to the perceived gains he had been afforded as result of his involvement with Satanism.
Keywords: Murderers -- Psychology; Criminal psychology; Satanism